Estudo da competitividade das empresas brasileiras do setor de fibras e filamentos qu??micos por meio do modelo de campos e armas da competi????o - Nave, Jo??o G??es Bizarro da (2007)
The word markets globalization accelerate the competition challenge within companies, irrespective of their size. One of the sectors most seriously affected by the opening of the Brazilian Economy is the textile sector, where the production processes suffered deep transformations during the last few years. Along the production chain of this important sector, the producers of artificial and synthetic fibers and filaments, focus of this work, introduced major technological progresses, products differentiation, added value and, consequently, a considerable upgrading of their final products. To better understand how the players of this sector compete within them, this research applies the ???Model of the Fields and Weapons of the Competition??? to each one individually. This model is used to formulate operational and business competitive strategies. The business strategy consists on the selection of the fields of competition while the operational strategy on the choice of the best weapons of competition. The first strategy is concentrated on the business as a whole and puts in evidence the image of the company towards its customers and competitors. The operational strategy refers to internal departments, puts in evidence the core of the organization and concentrates specifically on the use of the right weapons that will increase the competitiveness of the company. With the attained results it may be concluded that the most competitive and the less competitive companies follow the same business strategies. The calculations evidencing the influence of the operational competitive strategy show that the focus of this exercise is the mathematical variable that measure the criterion under which the company may turn competitive. This also proves the thesis of the ???Model of the Fields and Weapons of the Competition???, which indicates that ???to turn the company competitive does not exist more relevant conditions than operating only with the weapons that offer competitive advantages in the selected field to compete in the combined ???product/market???.